2019
DOI: 10.3390/rs11151763
|View full text |Cite
|
Sign up to set email alerts
|

Combining Color Indices and Textures of UAV-Based Digital Imagery for Rice LAI Estimation

Abstract: Leaf area index (LAI) is a fundamental indicator of plant growth status in agronomic and environmental studies. Due to rapid advances in unmanned aerial vehicle (UAV) and sensor technologies, UAV-based remote sensing is emerging as a promising solution for monitoring crop LAI with great flexibility and applicability. This study aimed to determine the feasibility of combining color and texture information derived from UAV-based digital images for estimating LAI of rice (Oryza sativa L.). Rice field trials were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
123
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(133 citation statements)
references
References 60 publications
9
123
1
Order By: Relevance
“…Light of different wavelengths has different effects on plant growth [42]. Image sensors mounted on UAVs are used to collect images of crops in different bands and extract different features [43,44]. The multi-spectral sensor we used (i.e., Airphen) is an imaging sensor.…”
Section: Discussionmentioning
confidence: 99%
“…Light of different wavelengths has different effects on plant growth [42]. Image sensors mounted on UAVs are used to collect images of crops in different bands and extract different features [43,44]. The multi-spectral sensor we used (i.e., Airphen) is an imaging sensor.…”
Section: Discussionmentioning
confidence: 99%
“…For agricultural crops, there exist, to our best knowledge, only two studies using texture features in combination with UAV multispectral information. In a multi-temporal study over two years, Zheng et al [48] and Li et al [49] used a multispectral sensor on a UAV to estimate rice biomass and LAI including different cultivars, varying seed densities and N levels. The authors concluded that the combination of spectral and texture information is a promising method for biomass estimation.…”
Section: Introductionmentioning
confidence: 99%
“…The imaging sensors mounted on the UAV mainly include hyperspectral, RGB, and multispectral sensors. They were reported to have a great performance for monitoring crop growth [11][12][13][14][15][16]. Compared with the former two, UAV-based multispectral sensors can acquire images with a spatial resolution from centimeter to decimeter level near the ground, achieving a better balance between cost and availability [17].…”
Section: Introductionmentioning
confidence: 99%